STRUKTUR KEPEMILIKAN DAN ARUS KAS BEBAS SEBAGAI PENENTU KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2009 â 2011 - Murdaniska Handayani, Vita (Students Journal of Economic and Management, 2012)
This study of the structure of ownership and free cash flow as a determinant of dividend policy on manufacturing companies in Indonesia Stock Exchange the period 2009 to 2011. This study aimed to examine (1) Is there any effect of ownership structure on corporate Dividend Policy Against Indonesia Stock Exchange in the period 2009-2011? and (2) Is there an effect of Free Cash Flow Dividend Policy Against the Indonesia Stock Exchange company in the period 2009 to 2011? The population in this study is a manufacturing company that went public the period 2009 - 2011 as many as 131 companies, while companies that do not pay dividends during the observation period were 106 firms that sample criteria set out above, acquired 25 companies manufacturing for a period of 3 years ie years 2009-2011 were used as samples in this study. Data analysis techniques using normality test, classical assumptions, the accuracy of the parameters, the accuracy of the model and the regression analysis. The results showed that: (1) Managerial Ownership has positive and significant impact on dividend policy so the higher the proportion of ownership by management, higher dividend policy administration, (2) Institutional Ownership positive but not significant effect on dividend policy, (3) cash flow positive but not significant effect on Dividend Policy. Based on these results it should be the future research agenda (1) Increase the number of observation periods in order to study samples obtained over the past 10 years many observations, (2) Adding other variables that may affect dividend policy (adjusted r square) as Return On Equity (Hanafi & Halim, 2005: 87) and market risk (Ismiyanti and Hanafi 2003), and (3) Conducting research in addition to manufacturing companies, but other companies are based sectors such as industry, industry-finance, transportation, telecommunications and so on, which is expected to give different results. Keywords: Ownership Structure, Cash Flow, Dividend Policy